Novel germplasm of tepary and other Phaseolus bean wild relatives from dry areas of Southwestern USA - Debouck, Daniel G.; Pratt, Richard C.; Dohle, Sarah; Porch, Timothy; Santaella, Marcela; Santos, Luis Guillermo; Urban, Milan O. (2025)
Heat and drought stresses threaten global bean production. Additional genetic resources are needed in genebanks for future improvement of bean crops through breeding for tolerance. The USA southwestern Sky Island mountains contain such genetic resources that have not been adequately collected nor characterized. Continuing the work done in 2023, a 9-day exploration in 2024 in southern New Mexico and Arizona for wild teparies and other Phaseolus species resulted in the collection of herbarium and seed samples of 18 populations of P. acutifolius, one each of P. angustissimus and P. filiformis, two of P. grayanus, three of P. maculatus and possibly three of P. montanus, or 28 populations in total. Samples of nodules and soil of rhizosphere were also collected. Outcomes and ways to improve the exploration endeavors are discussed.